2003
DOI: 10.1902/jop.2003.74.6.838
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Er:YAG and Diode Laser Irradiation on the Root Surface: Morphological and Thermal Analysis

Abstract: The application of Er:YAG and diode lasers at the utilized parameters did not induce high pulpal temperatures. Root surface irregularities were more pronounced after irradiation with an Er:YAG laser than with a diode laser.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
78
1
18

Year Published

2006
2006
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 229 publications
(99 citation statements)
references
References 30 publications
2
78
1
18
Order By: Relevance
“…The temperature rise of teeth placed in a 378C water bath after laser irradiation was reported to be 58C lower than the temperature rise of isolated teeth [34]. Nonetheless, the measurement of temperature rise is widely used as a convenient and fundamental method in evaluating the thermal effect of laser on pulp tissue [35][36][37], as the precisely controlled laboratory conditions can hardly be conducted in vivo.…”
Section: Discussionmentioning
confidence: 99%
“…The temperature rise of teeth placed in a 378C water bath after laser irradiation was reported to be 58C lower than the temperature rise of isolated teeth [34]. Nonetheless, the measurement of temperature rise is widely used as a convenient and fundamental method in evaluating the thermal effect of laser on pulp tissue [35][36][37], as the precisely controlled laboratory conditions can hardly be conducted in vivo.…”
Section: Discussionmentioning
confidence: 99%
“…3,4) Recently, the clinical use of lasers has increased, and lasers are now employed frequently even for endodontic treatment. 5,6) In particular, short wavelength Nd:YAG lasers and Ga-Al-As lasers are used for coagulation of deep tissue in the body, as well as for surgical treatment, hard tissue formation, and root canal therapy. [7][8][9] Against this background, we have been studying the anti-inflammatory effect of GaAl-As laser irradiation when used as an adjuvant to accelerate hard tissue formation.…”
mentioning
confidence: 99%
“…[49][50][51] The study by Theodoro et al showed that applying laser for 30 seconds with water spray can decrease temperature (-2.2 ± 2.5°C). 52 It should be taken into consideration that using too much water or air cooling results in energy absorption and decreased ablation effect of laser. 53 Another parameter that affects the antibacterial effect of laser, is radiation time.…”
Section: Anti-bacterial Effect Of Er:yag Laser On Enterococcus Faecalismentioning
confidence: 99%